Alexis de Tocqueville, historiador de la libertad posible - Cremades Ugarte, IGNACIO (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
We come across our author, Alexis de Tocqueville —with a very special mention of those passages of Democracy in America in which he paints a more sombre picture of the future of the freedoms of the individual— not only at the center of the controversy regarding the socialist critique of traditional European liberalism associated with Western democracy, but also in the discussion between those who, in the name of democracy and in consonance with theories on popular sovereignty, lean towards unconditional obedience to the will of the majority insofar as it incarnates reason, and those who consider that democracy is more a means than an end, that the majority is solely an opinion and not the manifestation of reason, and freedom a gift that must be nurtured, and therefore a costly acquisition, an arduous task of collective and —above all— personal edification.